University as a Business in the Perspectives of Chinese Hard Science Postgraduates - Ma, Yao (2016)
As the development trend of increasing marketization of universities, and more and more Chinese students choose UK for further study, this dissertation explores study life of Chinese postgraduates studying hard science courses in the University of Nottingham. The researcher consider that role of students have been converted to the consumers. The research was conducted by in-depth interviews following an interview guide that sought to the stories and experiences during their graduate studies in the University of Nottingham. Snowball sampling technique was employed for the data collection, and there were 6 Chinese participants involved in the interviews. It shows the process of university choosing, the complaints about the university and their perception of value for money.